Analisis Penerapan Pembebasan Bea Masuk atas Impor pada PT. X - Jeremia Tri Pamungkas; I Gede Agus Widyadana (Jurnal Titra, 2021)
PT. X is a logistical company and already has a network throughout Indonesia. PT. X has several modes of transportation to serve customers, one of which is ships. In order for the ship to continue to function properly, maintenance is needed, one of which is replacing some parts. Spare parts are usually imported from 3 countries, namely China, Japan and Korea. However, this study only focuses on imported goods from China. Imported goods will be charged with import fees by the customs. There is a way so that companies do not have to pay import duties, namely by requesting the Certificate of Origin (COO) Form E from the supplier. COO Form E is a special COO for goods imported from China. However, there are 91.49% of Form E that cannot be made in 2020. This study aims to analyze the reasons why import duties are not reduced/ exemptions, provide suggestions in order to maximize the possibility of obtaining a reduction/ exemption of import duties. The solution given is to create a checklist system created using Microsoft Excel Macro.